2002
DOI: 10.1063/1.1448909
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen beam generation system using pulsed laser evaporation of highly concentrated solid ozone

Abstract: A reactive oxygen beam generation system is described for the formation of high-quality and high-precision films. This system utilizes pulsed laser evaporation of highly concentrated solidified ozone (O3). The equipment for safely generating and handling a large amount of high-purity liquid and solid O3 was also developed for this purpose. The beam is characterized by its high concentration of oxygen atoms in an excited state [O(1D)], constant flux per laser shot (4×1017 molecules cm−2 shot−1), appropriate lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…However, oxidation by these sources has the following problems: ͑1͒ Energetically reactive ionic species may impair the grown film; ͑2͒ the number of radicals supplied to the Si surface is limited by the microwave power or light intensity of the apparatus; ͑3͒ nondestructive transportation of the generated radicals to the Si surface is difficult because of their short life resulting from mutual chemical reactivity (O ϩO→O 2 ). To overcome these problems, oxidation by highly concentrated ozone (O 3 ) gas under reduced pressure in cold-wall processing is considered to be promising for the following reasons: ͑1͒ The O 3 molecules have a long life as long as they are kept in a temperature-͑Ͻ100°C͒ and pressure-͑Ͻ44 000 Pa͒ controlled atmosphere, 7 thus enabling the effective transportation of O 3 to the surface; ͑2͒ O 3 can also be used as an in situ oxygen radical source by way of the O 3 decomposition reaction at the surface ͑i.e., O 3 →O 2 ϩO), 8 indicating that the number of supplied radicals can be increased by increasing the O 3 pressure at the surface; ͑3͒ the O 3 -formed SiO 2 film has been confirmed to have a more homogeneous structure with less Si displacement and a thin-ner transition layer at the SiO 2 /Si interface than thermally grown oxide 9,10 which would result in better electrical properties for the thin SiO 2 layer as a gate dielectric film.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, oxidation by these sources has the following problems: ͑1͒ Energetically reactive ionic species may impair the grown film; ͑2͒ the number of radicals supplied to the Si surface is limited by the microwave power or light intensity of the apparatus; ͑3͒ nondestructive transportation of the generated radicals to the Si surface is difficult because of their short life resulting from mutual chemical reactivity (O ϩO→O 2 ). To overcome these problems, oxidation by highly concentrated ozone (O 3 ) gas under reduced pressure in cold-wall processing is considered to be promising for the following reasons: ͑1͒ The O 3 molecules have a long life as long as they are kept in a temperature-͑Ͻ100°C͒ and pressure-͑Ͻ44 000 Pa͒ controlled atmosphere, 7 thus enabling the effective transportation of O 3 to the surface; ͑2͒ O 3 can also be used as an in situ oxygen radical source by way of the O 3 decomposition reaction at the surface ͑i.e., O 3 →O 2 ϩO), 8 indicating that the number of supplied radicals can be increased by increasing the O 3 pressure at the surface; ͑3͒ the O 3 -formed SiO 2 film has been confirmed to have a more homogeneous structure with less Si displacement and a thin-ner transition layer at the SiO 2 /Si interface than thermally grown oxide 9,10 which would result in better electrical properties for the thin SiO 2 layer as a gate dielectric film.…”
mentioning
confidence: 99%
“…Details of the operation of this generator have been described elsewhere. 7 To prevent a decrease in the concentration of O 3 gas during its flow to the Si surface, we applied lamp-heated cold-wall processing for oxidation. The results of our previous experiment suggested that, in ideal conditions that limit the heated area ͑Ͼ30°C͒ to just around the Si surface, the concentration of O 3 gas arriving at the Si surface was more than 93%.…”
mentioning
confidence: 99%
“…The ~100% O 3 was supplied using a pure ozone generator (Type: MPOG-SM1C1, Meidensha corp., Japan). The principles of the production method of the 100% ozone and the details of the pure ozone generator are described elsewhere [9][10][11][12]. The detail of the experimental setup is also described in a previous paper [5].…”
Section: Methodsmentioning
confidence: 99%
“…We estimated that the concentration of the HC ozone at the oxidation chamber was still above 90 vol % by thermal desorption spectroscopy (TDS) measurement at low temperatures. 7) Thus, the ozone gas concentration throughout the process is above 90 vol %. The sample was placed on the quartz susceptor for heating to 300 C by irradiation using the infrared lamp.…”
Section: Introductionmentioning
confidence: 99%